Una Propuesta Metodológica para Dimensionar el Impacto de los Vehículos Eléctricos sobre la Red Eléctrica - Ceballos Delgado, John Edward; Caicedo Bravo, Eduardo Francisco; Ospina Arango, Sandra (Ingeniería, 2016)
Context: Based on the projected trend of electric vehicles and charging stations, it is necessary to study how is the interaction between these new elements and the electrical network. For this, a review of literature on the impact of electric vehicles on the distribution networks, with reference to countries like Spain, Chile and Co-lombia was made. Method: Possible circuits that can be impacted by electric vehicles and the impact of different modes of transport in the electrical power quality, by simulations in MATLAB tool was determined. The information used for this research was obtained from various systems of enterprise management, the official website of the secretariats of mobility and UPME, research of domestic and foreign universities,Internet pages manufacturers of electric vehicles and charging stations, and IEEE standards, among others. Results: A series of stages, steps, activities, outputs and responsible was obtained, associated with electric models, for determining in an orderly manner, the impact of different modes of electrical transport in both the chargeability of the distribution system, and the quality of the energy at any point in the network. Also, a use case for a city in which enough information from their electrical circuits and location of possible installation sites of charging stations be taken validated. Conclusions: From the perspective of the application of the methodology in a use case, these results will determine how to adapt and change the infrastructure of the power grid sector companies, where there is a massive incursion of different modes of electric transportation.